Package plant of extended aeration membrane bioreactors: A study on aeration intensity and biofouling control - Ujang, Zaini (IWA Publishing, 2005)

(untitled)
Biofouling control is important for effective process of membrane bioreactor (MBR). In this study, phenomena of biofoulinq for immersed type extended aeration MBR with two different anti-fouling aeration intensities were studied through a laboratory set up. The objectives of this study were (a) to observe biofouling phenomena of MBR that operates under different anti-fouling bubbling intensity, and simultaneously monitors performance of the MBR in organic carbon and nutrients removal; (b) to compare effectiveness of detergent and detergent-enzyme cleaning solutions in recovering biofouled membranes that operated in the extended aeration MBR. For MBR, which operated under continuous anti-fouling aeration, deposition and accumulation of suspended biomass on membrane surface were prohibited. However, flux loss was inescapable that biofilm layer was the main problem. Membrane cleaning was successfully carried out with detergent-enzyme mixture solutions and its effectiveness was compared with result from cleaning with just detergent solution.